The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/nag.3290
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution for distributed torsional low strain integrity test for pipe pile

Abstract: Low strain integrity tests (LSITs) are the most popular non-destructive methods for pile testing. However, traditional LSITs have encountered unprecedented challenges as the need for long pile and existing pile testing keeps multiplying. Compared to traditional longitudinal excitations, the torsional wave is less influenced by the velocity attenuation effect and can be subjected at the pile shaft for existing piles. Distributed torsional LSIT is proposed in this article with the presentation of the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Nevertheless, steel and prestressed concrete pipe piles are also widely used in engineering practice. [46][47][48][49][50][51] Recently, the authors 52 proposed a rigorous continuum analytical model to describe the kinematic response of pipe piles subjected to seismic P-wave propagation. In this paper we present the extension of that model to account for shear S-waves, that arguably dominate the seismic response of piled foundations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, steel and prestressed concrete pipe piles are also widely used in engineering practice. [46][47][48][49][50][51] Recently, the authors 52 proposed a rigorous continuum analytical model to describe the kinematic response of pipe piles subjected to seismic P-wave propagation. In this paper we present the extension of that model to account for shear S-waves, that arguably dominate the seismic response of piled foundations.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned studies concern solid piles. Nevertheless, steel and prestressed concrete pipe piles are also widely used in engineering practice 46–51 . Recently, the authors 52 proposed a rigorous continuum analytical model to describe the kinematic response of pipe piles subjected to seismic P‐wave propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the development of the vibration theory of pile foundation, it can be seen that the pile-soil dynamic interaction models are alwaysthe main line of research regarding the vibration problems of pile foundation. In the field of the dynamic interaction between pile and PSS, there are three typical models, namely, the dynamic Winkler model [5][6][7][8][9][10][11][12][13], plain-strain model [14][15][16][17][18][19][20][21][22] and three-dimensional axisymmetric continuum model [23][24][25][26][27][28][29][30][31][32][33][34]. These models greatly promote the development of pile foundation dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Through literature research, it is found that two typical models are the most widely utilized. The first one is the rigid model, which assumes the PES to be a fixed boundary [6,14,23,25,26,30,33,35]. The rigid model is only suitable for end-bearing piles.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, more and more engineering activities have caused the change in the temperature eld of the surrounding soil layers, which inevitably a ects the physical and mechanical properties of the strata. ese engineering activities involve a broad range of civil engineering topics such as deep geological disposal of radioactive waste [1], deep drilling and excavation [2,3], extraction of geothermal energy [4][5][6], energy piles [7,8], ground improvement using prefabricated vertical thermal drain [9][10][11], oil and gas pipelines [12], and frictional heating-induced large-scale landslides [13]. is huge engineering demand has stimulated scholars to pay their attention on the thermo-hydromechanical coupling theory of porous media, especially the deformation properties of marine clay under a heat source [14].…”
Section: Introductionmentioning
confidence: 99%